PENGARUH PROFITABILITAS, LEVERAGE, INTENSITAS MODAL DAN PROPORSI DEWAN KOMISARIS INDEPENDEN TERHADAP TAX AVOIDANCE - Friska Atika Saputri (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
ABSTRACT Tax is a compulsory contribution of the state payable by a person to the state or entity as a taxpayer by not obtaining direct, coercive, and revoking taxes under the law. The purpose of this study is to illustrate the effect of profitability, leverage, capital intensity, and the proportion of independent board of commissioner against tax avoidance. This research is included in the type of quantitative research. Its population is all bank service sub sector companies listed in Indonesia stock exchange in 2012-2016. To test the hypothesis, used secondary data with purposive sampling method. Data analysis techniques use multiple linear regression with profitability, leverage, capital intensity and proportion of independent board of commissioners as variable (X) and tax avoidance as variable (Y). The result of data analysis shows that profitability and proportion of independent board of commissioner have negative effect to tax avoidance. While the leverage and capital intensity variables have no effect on tax avoidance. And profitability, leverage, capital intensity and proportion of independent board of directors influence simultaneously to tax avoidance.